2015
DOI: 10.1097/mao.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Results and Hearing Preservation With a Straight Narrow Electrode via Round Window Versus Cochleostomy Approach at Initial Activation

Abstract: The present results suggest that similar insertion depth and angle as well as similar low-frequency hearing preservation can be achieved in cochlear implantation with this straight narrow electrode via either cochleostomy approach or round window approach at least at initial activation. This fact gives the surgeon the opportunity to adapt access to the scala tympani as needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 23 publications
0
32
2
8
Order By: Relevance
“…Table 1 gathers results of clinical human studies comparing the RW versus the cochleostomy approach, showing that RW approach causes the same 10 11 or significantly less trauma to the cochlea. 12 13 …”
Section: Discussionmentioning
confidence: 99%
“…Table 1 gathers results of clinical human studies comparing the RW versus the cochleostomy approach, showing that RW approach causes the same 10 11 or significantly less trauma to the cochlea. 12 13 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hassepass et al reported a lower success rate than the former study. The author found that only 27 (65.8%) of 41 patients were able to undergo the RW approach during the CI surgery . In the current study, the RW approach was achieved in 70 (83.3%) of 84 patients.…”
Section: Discussionmentioning
confidence: 44%
“…We calculated the sample size using a two‐sided binomial test. The sample size was determined by setting the success rate of RW approach in the null proportion (P0) and the alternative proportion (P1) to 65% and 83% according to the previous study and this study, respectively. Type 1 error and type 2 error were set to 0.05 and 0.20, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors reported that similar levels of lowfrequency hearing preservation could be achieved using straight narrow electrode inserted with either approaches. [23][24][25] One possible difference contrasting both approaches is the relatively important anatomical variability of the round window itself, which could compromise insertion in certain cases and would make the cochleostomy a better option. 26 Extensive studies including more patients and looking at the detailed relationship between ore-operative anatomical characteristics of the RW region and how these should constrain the choice of the surgical approach are necessary.…”
mentioning
confidence: 99%